(untitled) (Al-Qamar, 2019)
Islam attaches great importance to equality between men and women in terms of marriage. This article presents a study of the texts, traditions and interpretations of scholars and jurists in this regard. It finds that if the goals of marriage are being achieved without adopting the Kufv, then there is no harm in ignoring it, but since there is a lot of wisdom behind keeping it in mind; it is generally considered necessary for marriage. As far as fatwas on various aspects of Kufv are concerned, those fatwas are not in line with the aims of Sharīʻah in which no criteria other than piety are included in Kufv, whereas in fatwas which include age, lineage, credibility in it are in accordance with the requirements of Sharīʻah.